Effect of taking chicken essence on cognitive functioning of normal stressed human volunteers - Md. Zain, Azhar; Jamil@Osman, Zubaidah; Naing, Khin Ohnmar@Noor Jan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Objective: This study evaluates the effect of a commercial brand of chicken essence (BEC) on the various parameters related to stress and cognition of human volunteers. BEC is produced by a hot-water extraction process from chicken meat under high pressure conditions. It contains concentrated amounts of proteins, amino acids and peptides such as carnosine compared to homemade traditional chicken soup. Due to the unique extraction process, it has been postulated that readily absorbed amino acids and bioactive peptides are present in BEC. Methods: In this study, we evaluated the effect BEC in comparison with a placebo on a group of distressed medical students. Students were randomly divided into two groups and given either BEC or a placebo drink daily for two weeks.Before and after the two weeks, the students were given a series of tests to asses their level of cognitive functioning and perceived stress level while being monitored for EEG recording. The combination of these tests, namely Digit span, Arithmetic and Letter-number sequencing, generally assessed the student's attention and working memory. Results: The working memory performance of student's who ingested essence of chicken was found to be significantly better than those who consumed placebo when data comparing baseline and after two weeks consumption were compared. Conclusion: This study seems to suggest that essence of chicken has positive effects on the subjects' cognitive functions.